Obesity and Diabetes Counseling for PPSU Officers in Kapuk Subdistrict, West Jakarta - Alvina, Alvina; Pusparini, Pusparini; Mario, Mario; Mashabi, Yasmine; Merijanti, Lie Tanu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Good performance and productivity of public infrastructure and facilities (PPSU) officers will have a positive impact on public services. Work productivity is influenced by physical fitness, nutritional status, work capacity, and additional burdens imposed by the work environment. Each individual's work productivity may differ depending on their nutritional status. Poor dietary status generally affects health, activities, and work productivity. Nutritional status is also related to anthropometric conditions, which dietary habits may influence. The dietary intake of PPSU officers is sometimes not considered in terms of food portions. A dietary intake of too much carbohydrate may increase blood glucose levels, thereby potentially causing diabetes. Dietary intakes of high-fat and carbohydrate content may also cause obesity. Diabetes and obesity can affect work performance, reducing productivity. This can be a problem for the productivity of PPSU officers. The purpose of implementing Community Service (PKM) is to provide education on the concepts of blood glucose levels and obesity, and on prevention through blood glucose level and obesity control. This knowledge needs to be imparted to PPSU officers. such that they may pay more attention to food intake and control blood glucose levels and BMI, thereby preventing diabetes and obesity and increasing work productivity. The implementation of PKM was carried out through counseling and Q&A involving 52 PPSU officers in Kapuk subdistrict, West Jakarta. The counseling results showed an increase in knowledge of obesity and diabetes among PPSU officers. Continuous counseling is needed for PPSU officers to prevent obesity and DM and increase work productivity.